Reinforcing polypropylene with graphene-polylactic acid microcapsules for fused-filament fabrication. (15th January 2021) - Aumnate, C.; Potiyaraj, P.; Saengow, C.; Giacomin, A.J.
Abstract: Fused-filament fabrication (FFF) is an extrusion-based form of three-dimensional (3D) printing for manufacturing parts rapidly. Commercially available polypropylene (PP) filaments produce shrinkage and warpage, termed dimensional instabilities, or have poor mechanical properties. FFF can therefore only produce prototypes. Polypropylene is a promising material, considering its 3D printed mechanical properties are as high as those from traditional manufacturing, yet, still exhibiting dimensional instabilities. In this work, we solve this instability problem by reinforcing PP with microcapsules. These microcapsules comprise polylactic acid (PLA) and reduced graphene oxide, confirmed by x-ray diffraction, x-ray photoelectron spectroscopy and Raman spectroscopy. By first encapsulating graphene with PLA, once melt-compounded, our scanning and transmitting electron microscopy shows that the PLA-graphene microcapsules are well dispersed throughout the PP main matrix. Our rheological analysis shows that our PP nanocomposites exhibit high melt elasticity, giving better support to printing constructs, and low viscosity, promoting printability, avoiding nozzle clogging and filament buckling. At 30% volume fraction, our nanocomposites also outperform the neat PP in mechanical testing. Graphical abstract: Unlabelled Image Highlights: A filament fabrication scheme that yields well-dispersed graphene-based microcapsules in polypropylene matrix. Our reinforced PP exhibits high melt strength, giving better support to printing constructs, and also low viscosity, enhancing printability. With light graphene loading (0.75 wt%), the printed construct neither shrinks nor warps. Our printed constructs with 30% volume fraction infill exhibit higher mechanical performance than neat PP.